Risk of pulmonary artery dissection in adults with congenital heart disease. (1st January 2023) - Egbe, Alexander C.; Miranda, William R.; Jain, C. Charles; Anderson, Jason H.; Stephens, Elizabeth H.; Andi, Kartik; Goda, Ahmed; Abozied, Omar; Ramachandran, Dhanya; Crestanello, Juan A.; Francois, Christopher; Connolly, Heidi M.
Abstract: Background: There are limited data about the risk of pulmonary artery (PA) dissection in adults with congenital heart disease (CHD), and the purpose of this study was to estimate the incidence of PA dissection in this population. Methods: Retrospective cohort study of adults with CHD that underwent cross-sectional imaging (2003–2020). PA aneurysm was defined as main or branch PA diameter > 40 mm or > 30 mm respectively, and severe PA aneurysm was defined as main or branch PA diameter > 50 mm. Results: Of 1, 673 patients (41 ± 10 years; male 58%), 493 (24%), 286 (19%), and 306 (20%) had aneurysms of the main, right, and left PA respectively, while 66 (4%) had severe PA aneurysm. During a median follow-up of 8.2 (interquartile range 3.7–10.3) years, there was one PA dissection in a patient with Eisenmenger syndrome, thus the incidence of PA dissection was 14 per 100, 000 patient-years. Of 779 females, 163 had one or more pregnancies during follow-up, and 41 (25%) of these patients had known PA aneurysm at the time of conception. There was no PA dissection during pregnancy. Of the 163 patients, 91 (56%) had cross-sectional imaging before and after pregnancy, there was no significant difference in PA dimension before versus after pregnancy (main PA 35 ± 5 versus 36 ± 4 mm, p = 0.6; right PA 21 ± 3 versus 33 ± 4 mm, p = 0.1; and left PA 23 ± 4 versus 22 ± 4 mm, p = 0.4). Conclusions: The risk of PA dissection was extremely low even in patients with severe PA aneurysm, or in patients with PA aneurysm that became pregnant. Collectively, these data suggest a benign natural history for patients without severe pulmonary hypertension and encourage and a conservative approach in managing patients with PA aneurysm. Graphical abstract: Unlabelled Image Highlights: The incidence of pulmonary artery (PA) dissection was low. Pregnancy was not associated with PA dissection. These data support conservative management for PA aneurysms.